Complex variables and applications - Churchill, Ruel V. (Ruel Vance) 1899-1987; Brown, James Ward (McGraw-Hill Education, 2014)
The text is designed to develop the theory that is prominent in applications of the subject. You will find a special emphasis given to the application of residues and conformal mappings. To accommodate the different calculus backgrounds of students, footnotes are given with references to other texts that contain proofs and discussions of the more delicate results in advanced calculus. Improvements in the text include extended explanations of theorems, greater detail in arguments, and the separation of topics into their own sections